Sweetcráve by Abid / Muhammad Abid Kamaruddin - Kamaruddin, Muhammad Abid (2021)
This report is completed as part of the requirement for the course Principles of Entrepreneurships (ENT53). The purpose of this report is to highlight the marketing strategy used by Sweetcráve by Abid. The completion of this work is fully by analysing the marketing posts of Sweetcráve by Abid on Facebook page. Sweetcráve by Abid has been registered under Companies Commission of Malaysia or Suruhanjaya Syarikat Malaysia (SSM) in May 2021. The business role is Dropshipper and categorised under Food & Beverages. Sweetcráve by Abid is established in 2021 and registered in March of the same year. Sweetcráve by Abid’s mission is to become dedicated producer and distributor of the said products, along with four core values which are quality, durability, innovation and community. While Sweetcráve by Abid’s vision is the be among the best and tastiest chocojar and chocolate cookies producer and distributor. Sweetcráve by Abid offers three products in total. They are Sweetcráve Choco Crunchy series that has two varieties under it. The varieties are Dark Crunch and Sweet Crunch that mainly use two different type of chocolates, which are dark and milk chocolate. The third product is Sweetcráve Chocolate Cookies that has a combination of a premium chocolate sauce and Biscoff Caramel Biscuits. The products are sold from RM14.90 to RM25.00. Sweetcráve by Abid Facebook page was created and has 763 total likes. The pre-launch post of Sweetcráve by Abid was made and posted on May 22 to create excitement among Facebook users. Sweetcráve by Abid officially launched on May 24. Sweetcráve by Abid has made a total of 12 hard sell posts that mainly focus on few elements such as price, ingredients and promotions. While there are six soft sell posts that covers the elements of awareness, customer service, reviews and informative knowledge.